The Effect of Guided Inquiry Learning Model Assisted Mind Map on Students’ Creative Thinking Ability - Pratama, I Putu Adi; Suwatra, Ignatius I Wayan; Wibawa, I Made Citra (International Journal of Elementary Education, 2020)
This research aims to determine the differences in the ability to think creatively between natural science students who used the Guided Inquiry learning model assisted with Mind Maps and students who were taught by using conventional learning on fourth grade elementary school students. This type of research was a quasi-experimental research with Non-Equivalent Post-test Only Control Group Design. The population of this research was numbered and the sample was 61 students taken by random sampling technique. Data collection was done by essay test technique. Data were analyzed by using inferential statistical analysis (t-test) with t-count = 3.021 and t-table = 1.671 Based on testing criteria, t-count> t-table (3.021,> 1.671). From the analysis of the data it was found that there was an influence of the Guided Inquiry learning model assisted with Mind Maps to the creative thinking abilities on the fourth grade elementary school students. The implication in this research was to use Guided Inquiry learning model assisted with Mind Maps could make students more active and happy because the Guided Inquiry learning model directly involves students in conducting experiments or research on a problem given by the teacher.